The role of alexithymia in the development of functional motor symptoms (conversion disorder) - Demartini, Benedetta (BMJ Publishing Group, 2014)
BACKGROUND: The mechanisms leading to the development of functional motor symptoms (FMS) are of pathophysiological and clinical relevance, yet are poorly understood. AIM: The aim of the present study was to evaluate whether impaired emotional processing at the cognitive level (alexithymia) is present in patients affected by FMS. We conducted a cross-sectional study in a population of patients with FMS and in two control groups (patients with organic movement disorders (OMD) and healthy volunteers). METHODS: 55 patients with FMS, 33 patients affected by OMD and 34 healthy volunteers were recruited. The assessment included the 20-item Toronto Alexithymia Scale (TAS-20), the Montgomery-Asberg Depression Rating Scale, the Reading the Mind in the Eyes’ Test and the Structured Clinical Interview for Personality Disorders. RESULTS: Alexithymia was present in 34.5% of patients with FMS, 9.1% with OMD and 5.9% of the healthy volunteers, which was significantly higher in the FMS group (χ(2) (2)=14.129, p<0.001), even after controlling for the severity of symptoms of depression. Group differences in mean scores were observed on both the difficulty identifying feelings and difficulty describing feelings dimensions of the TAS-20, whereas the externally orientated thinking subscale score was similar across the three groups. Regarding personality disorder, χ(2) analysis showed a significantly higher prominence of obsessive-compulsive personality disorder (OCPD) in the FMS group (χ(2) (2)=16.217, p<0.001) and 71.4% of those with OCPD also reached threshold criteria for alexithymia. CONCLUSIONS: Because alexithymia is a mental state denoting the inability to identify emotions at a cognitive level, one hypothesis is that some patients misattribute autonomic symptoms of anxiety, for example, tremor, paraesthesiae, paralysis, to that of a physical illness. Further work is required to understand the contribution of OCPD to the development of FMS.